2020
DOI: 10.1152/ajpendo.00334.2019
|View full text |Cite
|
Sign up to set email alerts
|

Dietary branched-chain amino acid restriction alters fuel selection and reduces triglyceride stores in hearts of Zucker fatty rats

Abstract: Elevations in circulating levels of branched-chain amino acids (BCAAs) are associated with a variety of cardiometabolic diseases and conditions. Restriction of dietary BCAAs in rodent models of obesity lowers circulating BCAA levels and improves whole-animal and skeletal-muscle insulin sensitivity and lipid homeostasis, but the impact of BCAA supply on heart metabolism has not been studied. Here, we report that feeding a BCAA-restricted chow diet to Zucker fatty rats (ZFRs) causes a shift in cardiac fuel metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 21 publications
2
38
1
Order By: Relevance
“…To determine if the robust reamination of KIV to valine applies to other BCKA, we also perfused isolated hearts with αketoisocaproate labeled in the 1-and 2-carbon positions ([1,2-13 C]KIC). Similar to our findings with labeled KIV, perfusion of hearts with [1,[2][3][4][5][6][7][8][9][10][11][12][13] C]KIC resulted in robust labeling of leucine (80.2 ± 4.6%) ( Supplementary Fig. 1a).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…To determine if the robust reamination of KIV to valine applies to other BCKA, we also perfused isolated hearts with αketoisocaproate labeled in the 1-and 2-carbon positions ([1,2-13 C]KIC). Similar to our findings with labeled KIV, perfusion of hearts with [1,[2][3][4][5][6][7][8][9][10][11][12][13] C]KIC resulted in robust labeling of leucine (80.2 ± 4.6%) ( Supplementary Fig. 1a).…”
Section: Resultssupporting
confidence: 88%
“…T he association of branched-chain amino acids (BCAA-valine, leucine, isoleucine) and their α-ketoacids (BCKA) with metabolic diseases such as obesity, insulin resistance, and diabetes are now well documented [1][2][3][4] , and mechanisms underlying these associations are beginning to emerge [5][6][7][8] . The role of BCKA metabolism in cardiac health and disease is less well understood.…”
mentioning
confidence: 99%
“…The role of a few amino acids in the maintenance of glycaemia via gluconeogenesis [ 89 , 106 ] is well known, but the focus is now on branched-chain amino acids [ 107 , 108 ]. These amino acids are catabolized to 2C fragments (leucine and isoleucine) and propionate (valine and isoleucine) [ 109 ] (nor a 3C but an important anaplerotic precursor of 4C fragments [ 110 ]).…”
Section: Enter the N: Amino Acids The Question Of Diversity Of Pamentioning
confidence: 99%
“…In addition, Wang et al (2011) found that five circulating branched-chain and aromatic amino acids (including leucine, isoleucine, valine, tyrosine and phenylalanine) might be used as early markers of diabetes risk. On the other hand, restriction of dietary BCAA by lowering of circulating BCAA levels improves whole-body and skeletal muscle insulin sensitivity in obese rats ( White et al, 2016 ) and lowers lipid accumulation in their hearts, which has positive impact on cardiometabolic health ( McGarrah et al, 2020 ) .…”
Section: Introductionmentioning
confidence: 99%